(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of the research is to identify the suitability of a patrol model in evaluating the financial performance of Iraqi banks. The financial reports of five Iraqi commercial banks were approved as a sample for research for the period from 2015 to 2020. The most common financial ratios were adopted for the purpose of measuring the five elements of the model, which are capital adequacy, profitability, credit risk, bankal efficiency and liquidity. The results showed the possibility of using the PATROL model in evaluating the performance of Iraqi banks, as it gave a realistic image of the reality of Iraqi banks in terms of high capital adequacy index and high liquidity, as well as fluctuation in profitability index, not to mention the problems of non-performing loans. The research recommends the adoption of a patrol model by the Central Bank of Iraq instead of the camels model that is currently adopted in evaluating the performance of Iraqi banks, due to the lack of full application of the camels model as shown by the guide to classify Iraqi banks, as the market sensitivity index is not being calculated because the Iraqi economy is an unstable economy and has been exposed to many Changes and shocks are what cause the difficulty of measuring this indicator in light of fluctuating market prices, so the patrol model is more suitable for the Iraqi environment because it is free from the indicator of the sensitivity of change to market prices.